PENINGKATAN PANGSA PASAR MELALUI CONTINUED USAGE INTENTIONS LAYANAN GOFOOD DI JAKARTA - ADELYNNA NOVIKA; NUNO SUTRISNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the influence of five components of consumption values (functional, emotional, social, conditional, and epistemic value) on the continued usage intentions of GoFood users in Jakarta. It employs a descriptive-causal research design with a five-point Likert scale. The sample was selected using purposive sampling, involving a total of 244 respondents, and utilized both primary and secondary data sources. Data were analyzed using multiple linear regression with the IBM SPSS Statistics 27 software. The results of this research indicate that all five components of consumption values have an effect on the continued usage intentions of GoFood users in Jakarta. These findings are expected to serve as strategic input for GoFood in its efforts to regain its dominant position in the app-based food delivery market.